Perbedaan Kadar Glukosa, Kadar Insulin, Homa IR Dan Protein Scube2 Pada Penderita DM Tipe 2 Terkontrol Dan Tidak Terkontrol - Safarti, Nisa Julia; Santosa, Budi -; Adhipireno, Purwanto (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2023)
Chronic diabetes mellitus is carried on by a rise in blood glucose levels as a result of decreased insulin sensitivity to manage blood sugar levels. The purpose of this study was to analyze participants with controlled and uncontrolled type 2 diabetes in relation of blood glucose, insulin, Homa-IR, and SCUBE2 protein levels. This study has a cross-sectional design and is descriptive analytic research. The sample for this study was stored biological fluid which was collected by total sampling from the Roemani Muhammadiyah Hospital Semarang Laboratory Installation in September 2022 to October 2022. The T-Independent test and the Mann-Whitney U-test used to the data analysis. The results of the T-Independent test results suggest that there was no significant variance between the insulin levels in DMT2 patients who were in control and those who unable (p=0.820, p>0.05). According to the results of the Mann-Whitney U-test analysis, there was no significant difference in the levels of scube2 protein between controlled and uncontrolled T2DM, and there was a significant difference in the glucose levels and Homa-IR values between controlled and uncontrolled T2DM, including both.but there was a significant effect of differences in glucose levels and Homa-IR values. The conclusion is that there are differences in glucose levels and Homa-IR values in controlled and uncontrolled DMT2 and there is no difference in insulin and scube 2 protein levels in controlled and uncontrolled DMT2.Â Â Keywords: Glucose, Insulin, Homa-IR, Protein Scube2